On the road to be an international Islamic capital market center - Harun, Mukaramah; Che Mat, Siti Hadijah (Jabatan Ekonomi Awam & Kewangan, Fakulti Ekonomi, Universiti Utara Malaysia, 2005)
This paper addresses the development of the Islamic debt securities in Malaysia with a focus on four key strategic initiatives that have been identified by Capital Market Master Plan to achieve the objective to establish Malaysia as an international Islamic capital market center. These initiative are, first, facilitate the development of a wide range of competitive products and services related to the Islamic capital market; second, create a viable market for the effective mobilization of funds; third ensure that there is an appropriate and comprehensive accounting, tax and regulatory framework for the Islamic capital market and fourth, enhance the value recognition of the Malaysian Islamic capital market internationally.